Anglo-American cultural influence in Slovenia - Sicherl, Eva (Acta neophilologica, 2018)
The article aims to address the growing tendency of Slovene native speakers towards borrowing English personal names when naming their new-borns. Statistical data confirm that foreign (and, with that, English) names have increased in the past decades, and statistical lists illustrate how in the case of personal names, "exoticisms" (e.g. Liam, Patrick, Nick, listed among the most popular 200 first names in the 2001-2015 period) compete with name forms that have been adapted and nativised long ago (e.g. Patrik), or are currently being introduced for the first time into Slovene. The influx of name borrowings from English is discussed from the point of view of pragmatic borrowing as advocated by Andersen (2014). A historical overview of the borrowing of English personal names into Slovene is given, and the role of English as the model discussed. Such pragmatically borrowed items carry significant sociolinguistic signals about the borrowers' attitudes, and these are analysed, based on questionnaires completed by parents of children aged 2-6. The significance of Anglo-American cultural influence is thus sought to be evaluated.
Keywords: angleščina; cultural influence; English; kulturni vpliv; osebna imena; personal names; Slovene; slovenščina